Pengaruh Konsentrasi PVA terhadap Stabilitas dan Aktivitas Antioksidan Masker Peel Off Ekstrak Kulit Jengkol (Archidendron pauciflorum (Benth.) Nielsen) - Zahrina Hanny Nabila; Ary Kristijono; Dara Pranidya Tilarso (Jurnal Sains dan Kesehatan, 2020)
Abstract Jengkol skin (Archidendron pauciflorum (Benth.) Nielsen) has antioxidant activity because it contains flavonoid compounds, saponins, and alkaloids, so jengkol skin can be used as a facial treatment. The peel off mask preparation was chosen because is one type of cosmetic that is easy to use because it utilizes the ability to release the film layer when applied to the skin so that it can increase comfort in use and is expected to increase the antioxidant activity of jengkol skin extract. Components of masks such as PVA (Polyvinyl Alcohol) which act as filming agents, affect the physical properties of the mask, because it is the material underlying the peel off mask. A stability test needs to be carried out to ensure the durability of the mask during storage. This study aims to determine the stability and antioxidant activity of peel off masks of jengkol skin from various concentrations of PVA. The method used is maceration with 70% ethanol solvent. PVA was used with concentrations of 6%, 8% and 10%. The physical properties test includes organoleptic test, pH test, homogenity test, adhesion test, dispersion test, dry time test, and viscosity test. The antioxidant test of peel off mask preparations was carried out by DPPH method (1,1 Difenyl-2-picrylhydrazil). Based on the results of the study, it was obtained that the peel off mask preparation was stable for a maximum of 21 days of storage. Formula with a PVA concentration of 10% is the formula that has the best physical properties during storage but is the most unstable formula because there are more white lumps than other formulas on the 28th day. The IC50 values ??were 420.9 ?g/mL, 397.4 ?g/mL and 434.1 ?g/mL